Nonaqueous electrolyte composition
By developing a non-aqueous electrolyte composition containing sodium salt and a specific solvent system, the problems of low solubility, insufficient conductivity and flammability of electrolyte composition in sodium ion batteries are solved, and the battery performance and safety are improved.
Patent Information
- Application Number
- CN202411987090.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-05-29
- Filing Date
- 2020-05-29
- Publication Date
- 2025-04-08
AI Technical Summary
The electrolyte compositions used in existing sodium ion batteries have problems such as low solubility, insufficient ionic conductivity and non-flammability, which affect the electrochemical performance and safety of the battery.
A new non-aqueous electrolyte composition is developed, comprising sodium salt-containing and specific solvent systems, including organic carbonate-based solvents and surfactants, preferably using propylene carbonate as the primary solvent, and improving the performance of the electrolyte by adding sulfur-containing compounds and flame retardants.
The electrolyte composition improves the electrochemical performance of sodium ion batteries, enhances the wettability of the membrane, improves the cycle life and capacity, and has the characteristics of non-flammability, improving the safety of the battery.
Smart Images

Figure CN119786741A_ABST
Abstract
Description
[0001] This application is a divisional application of the Chinese patent application entitled “Non-aqueous electrolyte composition” and application number 202080040092.X filed on May 29, 2020. This application claims priority to UK Patent Application No. 1907612.4 filed on May 29, 2019, the disclosure of which is incorporated herein by reference in its entirety. Field of the Invention
[0002] The present invention relates to a novel non-aqueous electrolyte composition, a sodium ion battery comprising the novel non-aqueous electrolyte composition, and an energy storage device comprising the non-aqueous electrolyte composition, such as a battery, a rechargeable battery, an electrochemical device, and an electrochromic device. Background of the Invention
[0004] Sodium-ion batteries are similar in many ways to the lithium-ion batteries commonly used today; they are both reusable secondary batteries that include an anode (negative electrode), a cathode (positive electrode), and electrolyte materials, both are capable of storing energy, and both are charged and discharged via similar reaction mechanisms. + (or Li + ) ions are deintercalated from the cathode and inserted into the anode. Simultaneously, charge-balancing electrons travel from the cathode through an external circuit containing the charger and into the anode of the battery. The same process occurs during discharge, but in the opposite direction.
[0005] Lithium-ion battery technology has gained a lot of attention in recent years and provides the preferred portable battery for most electronic devices used today. However, lithium is not a cheaply available metal and is considered too expensive for use in large-scale applications. In contrast, sodium-ion battery technology is still in its relative infancy, but is seen as advantageous; sodium is much more abundant than lithium, and some researchers predict that this will provide a cheaper and more durable way to store energy into the future, especially for large-scale applications, such as storing energy on the grid. However, there is still much work to be done before sodium-ion batteries become a commercial reality.
[0006] One area that requires increased attention is the development of suitable electrolyte compositions, particularly for sodium-ion batteries.
[0007] Although the design of suitable electrolyte compositions has received less attention than active materials (electrodes), their importance should not be overlooked as they are largely key to battery lifetime and determine the actual performance achievable by the battery, e.g. in terms of capacity, rate capability, safety, etc. However, to be a suitable electrolyte composition, it must satisfy a number of properties, these include:
[0008] Chemical stability - no reaction during battery operation, including within the electrolyte itself or with the separators, electrodes, current collectors or packaging materials used;
[0009] Electrochemical stability - there must be a wide electrochemical stability window, i.e. a large interval between the high and low onset potentials for decomposition by oxidation or reduction;
[0010] Thermal stability - the electrolyte composition must not decompose or chemically break down during normal battery operation and at operating temperatures
[0011] Physical properties - the electrolyte composition must be a liquid, so its melting and boiling points must be well above the internal operating temperature of the battery;
[0012] High ionic conductivity and low electronic conductivity are achieved through Na + Transmits the necessary power to maintain battery operation and minimize battery self-discharge;
[0013] Low toxicity;
[0014] Based on sustainable chemistry, i.e. made from abundant elements and via low-impact synthesis (energy, pollution, etc.) and
[0015] Cost-effective preparation.
[0016] In lithium-ion batteries, the most commonly used electrolyte compositions contain LiPF6 or LiBF4 dissolved in an organic carbonate-based solvent; electrolyte compositions containing 1M LiPF6 in a mixture of EC (ethylene carbonate) / DMC (dimethyl carbonate) or EC (ethylene carbonate) / EMC (ethyl methyl carbonate) are considered by most workers to be "standard" lithium-ion battery electrolytes.
[0017] In the case of sodium-ion batteries, the sodium analog NaPF6 can be used instead of LiPF6, but a much more cost-effective alternative is NaBF4; the latter also has the benefit of improved thermal stability compared to NaPF6. Unfortunately, however, NaBF4 has a very low solubility in organic carbonate-based electrolyte solvents, and this results in the ionic conductivity of the resulting electrolyte composition being generally too low for practical applications. Therefore, the poor solubility of NaBF4-containing electrolyte compositions in traditional organic carbonate-based solvents results in inferior electrochemical performance when compared to equivalent batteries using NaPF6.
[0018] Furthermore, it should also be noted that, although some materials used in lithium systems can be transferred to their sodium counterparts, it is by no means safe to assume that this will always be the case, in part because the atomic radius of sodium is larger than that of lithium. Therefore, a solvent system suitable for lithium-ion batteries may not be suitable for sodium-ion batteries, and vice versa. A prominent example of this difference is the incompatibility of propylene carbonate (PC) solvents in lithium-ion batteries with graphite anodes (the most commonly used anodes in current commercial lithium-ion systems). Due to this incompatibility, commercial lithium-ion batteries typically use EC / DMC or EC / EMC solvent systems, as described above. In contrast, sodium-ion systems will happily tolerate electrolyte solvents including PC.
[0019] However, it is desirable to find the optimal electrolyte solvent system for promoting the performance of high-Na-ion batteries.
[0020] It is therefore an object of the present invention to provide improved sodium ion conducting electrolyte compositions (i.e., they are electrolyte compositions designed for use in sodium ion secondary batteries) using sodium-containing salts dissolved in a suitable solvent system. The electrolyte compositions of the present invention will be cost-effective, will be non-flammable, will exhibit enhanced separator wettability, particularly when polyolefin separators are employed, and will exhibit excellent electrochemical performance in sodium ion batteries. The electrolyte compositions of the present invention will be particularly useful for sodium ion batteries employing an anode electrode comprising a non-graphite carbonaceous material, such as a hard carbonaceous material, or an anode electrode comprising a sodium insertion material or a conversion alloying anode material.
[0021] The present invention achieves these objects by providing a novel non-aqueous electrolyte composition comprising:
[0022] a) one or more sodium-containing salts; and
[0023] b) a solvent system comprising:
[0024] i) a first solvent component consisting of one or more organic carbonate-based solvents; and
[0025] ii) A second solvent component consisting of one or more surfactants in an amount of >0.5% to ≤10% by weight of the solvent system.
[0026] The one or more sodium-containing salts preferably contain one or more weakly coordinating anions. The term "weakly coordinating anion" or "WCA" is well known to those skilled in the art and is used to refer to anions containing several (more than one) elements, which may contain halogen atoms and / or oxygen atoms, and which share a single negative charge. This means that, for example, the negative charge is spread over the anion and makes the coordination ability of the anion relatively weak relative to the coordination ability of an anion with a concentrated negative charge or an anion with multiple negative charges. Preferably, the sodium-containing salt is selected from one or more of the formula NaM m X x Compounds of formula NaXO4; one or more fluorinated sulfonyl compounds; one or more fluorinated sulfonate compounds; one or more oxalato borate compounds; and tetrahedral anions such as tetrakis[3,5-bis(trifluoromethyl)phenylborate anion (B[3,5-(CF3)2C6H3]-4), tris(pentafluorophenyl)borate anion (B(C6F5) - 4) and tetracarboxy(trifluoromethyl)aluminate anion (Al[OC(CF3)3] - 4).
[0027] In one or more preferred formulas NaM m X x In the sodium-containing salt, M is one or more metals and / or non-metals and X is a group containing or consisting of one or more halogens, preferably selected from fluorine, chlorine, bromine and iodine, more preferably fluorine. The amount x of the halogen X is preferably x=1 to 16, more preferably x=4 or 6. The amount m of one or more metals and / or non-metals M is preferably m=1 to 3, more preferably m=1 to 2, and particularly preferably m=1. Ideally, the one or more metals and / or non-metals M are preferably selected from aluminum, boron, gallium, indium, iridium, platinum, scandium, yttrium, lanthanum, antimony, arsenic and phosphorus. Particularly preferably, M is selected from aluminum, boron, gallium, phosphorus and arsenic. The most preferred general formula NaMnX x The sodium salt is selected from one or more of sodium tetrafluoroborate (NaBF4) and sodium hexafluorophosphate (NaPF6).
[0028] In the preferred sodium compound of one or more formula NaXO4, element X is preferably one or more halogens selected from fluorine, chlorine, bromine and iodine. Chlorine is particularly preferred, and the most preferred sodium salt of formula NaXO4 is NaClO4.
[0029] Preferred sodium salts of one or more fluorine-containing sulfonyl compounds and / or sodium salts of one or more fluorine-containing sulfonate compounds include:
[0030] Sodium trifluoromethanesulfonate, also known as sodium trifluoromethanesulfonate or NaOTf(CF3NaSO3);
[0031] Sodium bis(fluorosulfonyl)imide, also known as NaFSI (NaN(SO2F)2); and
[0032] Sodium bis(trifluoromethanesulfonyl)imide, also known as NaTFSI (C2F6NNaO4S2).
[0033] Preferred sodium salts of one or more oxalatoborate compounds include:
[0034] Sodium bis(oxalate), also known as borate NaBOB or NaB(C2O4)2; and
[0035] Sodium difluoro(oxalato)borate, also known as NaDFOB.
[0036] The amount of the one or more sodium-containing salts is conveniently expressed as "molar concentration of the component in a) in the solvent system b)"; that is, the total number of moles of the one or more sodium-containing salts per liter of the solvent system b). Preferably, the molar concentration of each sodium-containing salt in a) is individually in the range of 0.1M to 5M, and further preferably in the range of 0.1M to ≤2M. Very preferably, in particular when the component in a) is NaBF4 or NaPF6, the molar concentration is in the range of 0.1M to ≤2M. The combined total molar concentration of all sodium-containing salts in a) is preferably in the range of 0.1M to 10M, and more preferably in the range of 0.1M to 6M, and most preferably in the range of 0.1M to ≤4M.
[0037] The one or more organic carbonate-based solvents present in the first solvent component i) may be cyclic or acyclic compounds, characterized in that they contain a carbonate group, i.e. a carbonyl group flanked by one or two alkoxy groups: R1O(C=O)OR2. The R1 and R2 groups are preferably independently selected (i.e. they may be identical or different from each other) from hydrogen; or C1 to C 20 - a cyclic or acyclic, branched or unbranched, substituted or unsubstituted alkyl group; or C1 to C 20 - a cyclic or acyclic, branched or unbranched, substituted or unsubstituted alkenyl group; or C1 to C 20 - branched or unbranched, substituted or unsubstituted cycloalkyl-, phenyl- or heterocyclic-containing groups. Very suitable electrolyte solvents include C3-C 10Cycloalkyl organic carbonates, such as propylene carbonate (C4H6O3) and ethylene carbonate (C3H4O3). Propylene carbonate (C4H6O3) shows particularly favorable compatibility with electrode materials, and the high solubility, wide liquidus range and high boiling point of the material also make this solvent favorable for use in sodium ion batteries. Other very suitable organic carbonate-based compounds include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethylene carbonate (EC), ethyl methyl carbonate (EMC), fluoroethylene carbonate (FEC) and vinylene carbonate (VC).
[0038] A highly preferred electrolyte composition of the present invention comprises a first solvent component consisting of propylene carbonate alone or alternatively a combination of propylene carbonate and one or more other organic carbonate-based compounds. When a mixture of organic carbonate-based compounds is used, the amount of each of the one or more organic carbonate-based solvents is conveniently expressed in terms of a weight ratio. For example, a preferred organic carbonate-based solvent may comprise a mixture of ethylene carbonate, diethyl carbonate, and propylene carbonate, and this will ideally be in a weight ratio range of 1 to 4: 1 to 10: 1 to 10 weight / weight, and further ideally in a weight ratio of 1 to 3: 1 to 5: 1 to 5 weight / weight, and most ideally 1: 2: 1 weight / weight.
[0039] The electrolyte composition of the present invention is very advantageous and contains propylene carbonate in an amount of at least 40%, preferably at least 50%, and further preferably at least 60% by weight of the organic carbonate-based solvent. Very preferably, propylene carbonate is the only organic carbonate-based solvent, i.e. it is present in an amount of 100% by weight of the organic carbonate-based solvent.
[0040] The preferred electrolyte composition of the present invention comprises a mixture of ethylene carbonate and diethyl carbonate without propylene carbonate. These organic carbonate-based components are preferably present in a weight ratio of 1 to 20: 1 to 20 weight / weight, further preferably in a weight ratio of 1 to 10: 1 to 10 weight / weight, further preferably in a weight ratio of 1 to 5: 1 to 5 weight / weight, and most preferably in a weight ratio of 1: 1 weight / weight.
[0041] Preferably, one or more surfactants used in the second solvent component ii) of the present invention are selected to enhance the ability of the electrolyte composition to wet the separator (especially the polyolefin separator) of the battery, which in turn advantageously promotes a longer battery cycle life. Such surfactants are ideally selected from one or more of the following:
[0042] 1) Anionic (negatively charged) surfactants. Suitable examples include: carboxylates, such as alkyl carboxylates (e.g., fatty acid salts), carboxylate fluorosurfactants; sulfates, such as alkyl sulfates (e.g., sodium lauryl sulfate), alkyl ether sulfates (e.g., sodium lauryl ether sulfate); sulfonates: docusates (e.g., sodium dioctyl sulfosuccinate), alkylbenzene sulfonates; phosphate esters, such as alkyl aryl ether phosphates and alkyl ether phosphates.
[0043] 2) Zwitterionic (amphoteric) surfactants, which can be anionic, cationic or nonionic, depending on the pH of the solution in which they are located. Examples include: RN + H2CH2COO - , RN + (CH3)2CH2CH2SO3 - , phospholipids such as phosphatidylcholine (lecithin);
[0044] 3) Cationic surfactants with positive charge, such as RN + H3Cl - , RN + (CH3)3Cl - , dioctadecyldimethylammonium chloride, cetylpyridinium chloride, benzalkonium chloride, cetyltrimethylammonium chloride (CTAC), and cetyltrimethylammonium bromide (CTAB); and
[0045] 4) Nonionic surfactants. These are uncharged and examples include: polyol esters (e.g., glycols, glycerides, sorbitan and sorbitan derivatives, such as fatty acid esters of sorbitan (Spans) and their ethoxylated derivatives (Tweens)), polyoxyethylene esters and poloxamers containing block copolymers, such as poloxamer 84, poloxamer 105, poloxamer 123, poloxamer 124, poloxamer 188, poloxamer 237, poloxamer 338, poloxamer 407 and poloxamer F127.
[0046] Most preferably, the second solvent component ii) of the electrolyte composition of the present invention contains one or more surfactants containing nonionic block copolymers.
[0047] Based on the total weight of the electrolyte solvent system used in the electrolyte composition, the total amount of one or more surfactants used in the electrolyte composition of the present invention is >0.5 to ≤10% by weight of the solvent system, preferably ≥0.6 to ≤6% by weight of the solvent system, further preferably ≥0.6 to ≤4 weight %, very preferably ≥0.6 to ≤3 weight %, and ideally 0.6 weight % to ≤2.5 weight %.
[0048] In a preferred embodiment, the non-aqueous electrolyte composition according to the present invention further comprises at least one additional compound which may or may not be a solvent, and the additional compound is preferably selected from sulfur-containing compounds, flame retardant compounds (such as compounds containing polyalkyl phosphates, preferably compounds containing non-fluorinated polyalkyl phosphates), diluents (such as compounds containing hydrofluoroethers, preferably compounds containing hydrofluoroalkyl ethers), glycol diethers (also known as "glyme"), glycol ether acetates, ionic liquids, nitrile-containing compounds (such as adiponitrile, glutaronitrile), and any solvent capable of promoting a decrease in electrolyte viscosity by acting as an inert diluent (such as hydrofluoroalkyl ethers, preferably 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (HFE or TTE)). For the avoidance of doubt, the at least one additional compound does not include any organic carbonate-based solvent listed in the first solvent component, or a surfactant as listed in the second solvent component.
[0049] Suitable sulfur-containing compounds include cyclic and / or non-cyclic sulfur-containing compounds, and are preferably selected to be able to form a stable cathode-electrolyte interphase (CEI) on the cathode and / or to form a stable solid electrolyte interphase (SEI) on the anode, which in turn leads to advantages such as enhanced first cycle coulombic efficiency and cycle life enhancement. Preferably, one or more sulfide compounds are sulfones, i.e., they have a sulfonyl functional group connected to two carbon atoms. The central hexavalent sulfur atom is double-bonded to each of the two oxygen atoms and has a single bond connection to each of the two carbon atoms. Such compounds have the general formula R-SO2-R', wherein R and R' can be independently selected from (i.e. they can be the same or different from each other) any linear or branched, substituted or unsubstituted C1 to C6-alkyl group; linear or branched, substituted or unsubstituted C1 to C6-alkenyl group; linear or branched, substituted or unsubstituted C1 to C6-alkoxy group; or substituted or unsubstituted C3-C6-cycloalkyl-, phenyl- or heterocyclic-containing group. Further preferably, the sulfide compound is selected from cyclic sulfones, non-cyclic sulfones and cyclic sultones. Suitable examples include sulfolane ((CH2)4SO2), 3-methylsulfolane ((CH3)CH(CH2)3SO2), 1,3-propylene glycol cyclosulfate (PCS), also known as 1,3,2-dioxathiazole 2,2-dioxide (DTD or (CH2)3SO4), trimethyl sulfone, 1-propylene 1,3-sultone ((CH)2CH2SO 3), 1,3-propane sultone (CH2)3SO3, trimethylanesulfone ((CH2)3SO2) and methyl phenyl sulfone ((CH3)(C6H5)SO2). Particularly preferred are one or more cyclic sulfones and / or cyclic sultones and / or 1,3-propylene glycol cyclic sulfate. Very preferably, the sulfur-containing compound used in the solvent system does not contain a sulfoxide-containing compound, a sulfite-containing compound or a sulfide-containing compound, and ideally, the electrolyte composition does not contain a sulfoxide-containing compound, a sulfite-containing compound or a sulfide-containing compound.
[0050] When used in the electrolyte composition of the present invention, the total amount of one or more sulfur-based compounds is preferably ≤80 wt %, further preferably ≤60 wt %, ideally 0 wt % to ≤60 wt %, and most ideally 1 wt % to ≤55 wt %, based on the total weight of the solvent system used in the electrolyte composition.
[0051] Suitable optional flame retardant materials include one or more polyalkyl phosphate-containing compounds, which, when present in the electrolyte composition of the present invention, not only advantageously produce batteries with reduced flammability compared to conventional organic carbonate electrolytes lacking polyalkyl phosphate-containing compounds, but their use has been found to significantly enhance battery cycle life, as well as promote favorable separator wetting, particularly in the case of polyolefin separator wetting.
[0052] Suitable polyalkyl phosphates include trialkyl phosphates, with trimethyl phosphate and / or triethyl phosphate being particularly preferred.
[0053] When used in the electrolyte composition of the present invention, the total amount of one or more polyalkyl phosphate-containing compounds is preferably at least 1 wt % to 90 wt %, further preferably at least 2 wt % to 70 wt %, more preferably at least 5 wt % to 70 wt %, and ideally greater than 10 wt % to 70 wt % of the total weight of the solvent system used in the electrolyte composition. In some embodiments, it is found that <5 wt % of the amount of one or more polyalkyl phosphate-containing compounds effectively reduces flammability and / or enhances cycle life and / or increases the wettability of the separator.
[0054] Suitable glycol dimethyl ethers can be selected from: ethylene glycol dimethyl ether (monoglycol dimethyl ether CH3-O-CH2 CH2-O-CH3); diethylene glycol dimethyl ether (diglyme CH3-O-(CH2-O)2-CH3); triethylene glycol dimethyl ether (triethylene glycol dimethyl ether, CH3-O-(CH2-O)3-CH3); tetraethylene glycol dimethyl ether (tetraethylene glycol dimethyl ether, CH3-O-(CH2-O)4-CH3); ethylene glycol diethyl ether (ethyl glycol dimethyl ether, CH3CH2-O-CH2CH2-O-CH2CH3); diethylene glycol dimethyl ether (triethylene glycol dimethyl ether, CH3-O-(CH2-O)3-CH3); tetraethylene glycol dimethyl ether (tetraethylene glycol dimethyl ether, CH3-O-(CH2-O)4-CH3); Ether (ethyl diglyme, CH3CH2-O-(CH2-O)2-CH2CH3); diethylene glycol dibutyl ether (butyl diglyme, CH3CH2CH2-O-(CH2-O)2-CH2CH3); poly(ethylene glycol) dimethyl ether (polyethylene glycol dimethyl ether, CH3-O-(CH2-O)n-CH3); and dipropylene glycol dimethyl ether (propylene glycol dimethyl ether, CH3-O-(CH2CHCH3-O)2-CH3).
[0055] Particular preference is given to diethylene glycol dimethyl ether (diglyme), triethylene glycol dimethyl ether (triglyme) and tetraethylene glycol dimethyl ether (tetraglyme).
[0056] Suitable one or more glycol ether acetates may be selected from: propylene glycol methyl ether acetate; dipropylene glycol methyl ether acetate; ethylene glycol monobutyl ether acetate; ethylene glycol monomethyl ether acetate; ethylene glycol monoethyl ether acetate; diethylene glycol monobutyl ether acetate; diethylene glycol monoethyl ether acetate; and diethylene glycol monoethyl ether acetate.
[0057] Ethylene glycol monomethyl ether acetate and ethylene glycol monoethyl ether acetate are particularly preferred.
[0058] Suitable ionic liquids may incorporate any of the following: cations based on the imidazolium, pyrrolidinium and ammonium families, and cations based on tetrafluoroborate (BF4 - ), bis(fluorosulfonyl)imide (FSI), tris(fluoromethanesulfonyl)imide (TFSI), perchlorate (ClO4 - ), hexafluorophosphate (PF6 - ) and the anion of ferric perchlorate (FeCl4-).
[0059] The amount of one or more additional compounds used in the electrolyte composition of the present invention is preferably in the range of 0.1 wt % to 80 wt %, preferably 0.1 wt % to 70 wt %, further preferably 0.2 wt % to 55 wt %, and most preferably 0.5 wt % to 50 wt %, based on the total weight of the solvent system used in the electrolyte composition.
[0060] The electrolyte composition according to the present invention may also optionally include one or more performance additives, the amount of which is generally <15% by weight of the total weight of the solvent system used in the electrolyte composition, preferably <10% by weight, and further preferably 0.1% by weight to <5% by weight, and preferably acts at the electrolyte-electrode interface rather than in the bulk of the electrolyte. Such performance additives are useful, particularly in liquid electrolyte systems, where insoluble degradation products form a solid passivation layer (SEI) on the surface of the negative electrode to optimize the ionic and electronic conductivity of the SEI and also maximize its strength and adhesion to the surface of the negative electrode. Performance additives can also be used to increase the wetting of the diaphragm surface, protect the battery from overcharge events, and serve as fluidity enhancers, viscosity reducers and / or impurity or free radical scavengers. In addition, such performance additives can bring additional benefits to battery performance, such as providing fault protection in the event of overcharging of the battery or imparting further non-flammable properties to the electrolyte.
[0061] Suitable performance additives may be selected from: polymerizable additives for promoting overcharge protection, such as biphenyl, diphenylamine, dimethoxydiphenylsilane (DDS), 3-chloroanisole (3CA), N-phenylmaleimide, xylene (methyl substituted benzene) and cyclohexylbenzene; additives based on redox shuttle mechanisms for promoting overcharge protection, such as 2,5-di-tert-butyl-1,4-dimethoxybenzene (DDB), 4-tert-butyl-1,2-dimethoxybenzene (TDB), 1,4-bis(trimethylsilyl)-2,5-dimethoxybenzene (BT MSDB) and 1,4-bis(2-methoxyethoxy)-2,5-di-tert-butylbenzene; additives for imparting further flame retardant properties to the electrolyte, such as dimethyl methylphosphonate (DMMP), ethoxy-pentafluoro-cyclotriphosphazene (N3P3F5OCH2CH3, EFPN), tris(2,2,2-trifluoroethyl)phosphite and / or tris(2,2,2-trifluoroethyl)phosphate (TFEP), methyl nonafluorobutyl ether (MFE) and silane-A12O3 nanoparticles; and additives for promoting better high temperature cycling, such as succinic anhydride.
[0062] The electrolyte composition of the present invention is preferably used in a sodium ion battery. Therefore, in another aspect, the present invention provides a sodium ion battery comprising a negative electrode, a positive electrode and the electrolyte composition according to the present invention. Such a sodium ion battery can be used in energy storage devices such as batteries, rechargeable batteries, electrochemical devices and electrochromic devices.
[0063] Ideally, the electrolyte composition of the present invention is used in a sodium ion battery using a carbonaceous material as an active negative (anode) electrode material. Preferably, the carbonaceous material is a non-graphitizable carbonaceous material. Such carbon materials include, but are not limited to, modified graphite carbon, non-graphite carbon, isotropic carbon, partially graphite carbon, exfoliated graphite, expanded graphite, amorphous carbon, non-crystalline carbon, soft carbon, and hard carbon materials. For the avoidance of doubt, "non-graphitizable carbon material" as used herein does not include any carbon having a natural graphite structure with long-range order (which is ubiquitous in the bulk of the structure) or a synthetic graphite material having a structure identical to that of a natural graphite material. A typical method for preparing non-graphitizable carbon employs heating a starting material, such as sucrose, corn starch, glucose, an organic polymer (such as polyacrylonitrile or resorcinol-formaldehyde gel), cellulose, petroleum coke, or asphalt coke to about 1200°C. Commercially available non-graphitizable carbon materials are referred to as "hard carbon materials" and include products from Kureha Corporation under the trade name "Carbotron TM Hard Carbon Materials" and those sold under the names of "Bio-Carbotron TM Those sold under the name of "hard carbon materials".
[0064] Ideally, the sodium ion battery of the present invention uses an anode active material containing non-graphitizable carbon (e.g., hard carbon) alone, however, it is also advantageous to use a material that combines non-graphitizable carbon with one or more other materials, such as a metal or alloy that can store sodium, or a metal or non-metal in the form of its element or compound (as a mixture or as a composite). Particularly preferred anode active materials include hard carbon / X materials, where X can be one or more elements such as antimony, tin, phosphorus, sulfur, boron, aluminum, gallium, indium, germanium, lead, arsenic, bismuth, titanium, molybdenum, selenium, tellurium, silicon or carbon. Hard carbon / Sb, hard carbon / Sn, hard carbon / Sb x Sn y and hard carbon / P are suitable hard carbon-containing materials.
[0065] A non-graphitizable carbon material known as "expanded" or "exfoliated" graphite has a structure identifiable as similar to that of natural graphite but not identical thereto because it is modified so that its carbon exhibits an interlayer spacing in the (001) direction greater than 3.35 angstroms.
[0066] Most preferably, the nonaqueous electrolyte composition of the present invention is used with an anode comprising non-graphitizable carbon, preferably a hard carbon anode.
[0067] Thus, in a very preferred embodiment, the present invention provides the above non-aqueous electrolyte composition, which is suitable for use in a sodium ion battery containing an anode comprising a non-graphitizable carbon material, preferably a hard carbon anode.
[0068] In an alternative example, the electrolyte composition of the present invention can be used in a sodium ion battery, which uses a sodium insertion material such as a titanate compound (undoped or doped with a small amount of various other metals and / or replaced by other transition metals Ti and / or replaced by other halogens O), for example Na2Ti3O7; NaHTi3O7; Na2Ti6O 13 ;Na2Li2Ti5O 12 , K2Ti3O7, K2Ti6O 13 , TiO2, NaTiO2 and H2Ti3O7 anodes. Other sodium insertion materials, such as undoped or doped (with small amounts of various other metals and / or halogens) or partially substituted (with any metal, non-metal, metalloid and / or halogen) NaTi2(PO4)3 and TiS2, either in combination with or as a substitute for non-graphitizable carbon materials.
[0069] In another alternative example, the electrolyte composition of the present invention can be used in a sodium ion battery, which employs an anode comprising a conversion and / or alloying material and a material that exhibits a conversion and alloying type reaction mechanism to store sodium, such as tin, antimony, molybdenum, phosphorus, sulfur, indium, lead, iron, manganese and germanium, in elemental form or in compound form, preferably containing one or more selected from oxygen, carbon, nitrogen, phosphorus, sulfur, silicon, fluorine, chlorine, bromine and iodine (such as SnO, SnO2, SnF2, SiP2, Fe2O3, Fe3O4, FeS, FeS2, MoS2, MoO3, Sb, Sb2O3, SnSb and SbO), in combination with a non-graphitizable carbon material or as a substitute thereof.
[0070] Secondary carbonaceous materials may also be used in combination with the above-mentioned anode active materials, especially to improve the conductivity of the anode, such as activated carbon materials, particulate carbon black materials, graphene, carbon nanotubes and graphite. Examples of particulate carbon black materials include: "C65 TM Carbon (also known as Super p TM Carbon black) (BET nitrogen surface area 62m 2 / g) (available from Timcal Limited), although BET nitrogen surface areas < 900 m 2 / g other carbon black, such as "Ensaco 350g TM ”, which is a BET nitrogen surface area of 770m 2 / g of carbon black (available from Imerys Graphite and Carbon Limited as a specialty carbon for rubber compositions). The BET nitrogen surface area of the carbon nanotubes is 100-1000 m 2 / g, graphene is about 2630m 2 / g, and the BET nitrogen surface area of activated carbon materials is >3000m 2 / g.
[0071] The present invention also provides a sodium ion battery comprising a negative electrode, a positive electrode and a non-aqueous electrolyte composition according to the present invention as described above, wherein the negative electrode comprises a non-graphitizable carbon material, preferably a hard carbon material. Such a sodium ion battery can be used in energy storage devices such as batteries, rechargeable batteries, electrochemical devices and electrochromic devices. When used in a sodium ion battery comprising a polyolefin separator, it is found that the electrolyte composition according to the present invention is particularly useful.
[0072] The sodium ion secondary battery according to the present invention may contain any cathode electrode active material, however, the preferred cathode electrode active material has the general formula:
[0073] A 1±δ M 1 v M 2 w M 3 x M 4 Y M 5 Z O 2-c
[0074] in
[0075] A is one or more alkali metals selected from sodium, potassium and lithium;
[0076] M 1 comprising one or more redox-active metals in oxidation state +2, preferably selected from nickel, copper, cobalt and manganese;
[0077] M 2 Contains metals in an oxidation state greater than 0 to less than or equal to +4;
[0078] M 3 Contains a metal in oxidation state +2;
[0079] M 4 Contains metals in an oxidation state greater than 0 to less than or equal to +4;
[0080] M 5 Contains metal in oxidation state +3;
[0081] in
[0082] 0≤δ≤1;
[0083] V>0;
[0084] W>0;
[0085] X>0;
[0086] Y ≥ 0;
[0087] At least one of W and Y>0
[0088] Z>0;
[0089] C is in the range of 0≤c<2
[0090] Wherein V, W, X, Y, Z and C are selected to maintain electrochemical neutrality.
[0091] Ideally, metal M 2 Contains one or more transition metals and is preferably selected from manganese, titanium and zirconium; M 3 Preferably, it is one or more selected from magnesium, calcium, copper, tin, zinc and cobalt; M 4 comprises one or more transition metals, preferably selected from manganese, titanium and zirconium; and M 5 Preferred are one or more selected from aluminum, iron, cobalt, tin, molybdenum, chromium, vanadium, scandium and yttrium.
[0092] Particularly preferred cathode electrode active materials will be nickelate based materials.
[0093] Cathode electrode active materials having any crystal structure may be used, however, preferably the structure will be O3 or P2 or a derivative thereof, but, in particular, it is also possible that the cathode electrode active material will contain a mixture of phases, i.e. it will have an inhomogeneous structure consisting of several different crystal forms. For example, the cathode active material will contain compounds having the general formula detailed above in a mixture of O3 and P2 phases. The ratio of O3:P2 phases is preferably 1 to 99:99 to 1.
[0094] As demonstrated in the specific examples presented below, the electrolyte compositions of the present invention provide surprising and significant advantages, particularly in terms of enhanced cycle life, as well as enhanced capacity and non-flammability, when compared to electrolyte compositions that are not compositions of the present invention, i.e., compared to compounds that do not include one or more organic carbonate-based solvents in combination with one or more surfactants as described above.
[0095] In an alternative aspect, a non-aqueous electrolyte composition is provided, comprising: a) one or more sodium salts; and b) a solvent system comprising i) a first solvent component comprising one or more organic carbonate-based solvents, and ii) a second solvent component comprising at least one compound selected from glycol dimethyl ether, glycol ether acetate, ionic liquid, nitrile-containing compound, diluent (such as hydrofluoroalkyl ether diluent), sulfur-containing compound and flame retardant (such as polyalkyl phosphate-containing compound); optionally in combination with one or more surfactants. Preferably, suitable glycol dimethyl ether, glycol ether acetate, ionic liquid, nitrile-containing compound, diluent, hydrofluoroalkyl ether diluent, sulfur-containing compound, flame retardant, polyalkyl phosphate-containing compound and surfactant are as described above.
[0096] In another alternative aspect, a sodium ion battery and an energy storage device are provided, which include the non-aqueous electrolyte composition according to the above alternative aspects. BRIEF DESCRIPTION OF THE DRAWINGS
[0098] The present invention will now be described with reference to the following drawings, in which:
[0099] Figure 1a shows the absorption of ND525 separator (Asahi Kasei Corporation) for electrolyte compositions according to the present invention (samples TEL 3, TEL 3a, TEL 3b, TEL 4, TEL 4a, and TEL 4b) compared to the absorption of a cell using a control electrolyte composition (sample TEL 0);
[0100] Figure 1b The electrolyte uptake by the hard carbon electrodes for the electrolyte compositions of the invention (samples TEL 3, TEL 3a, TEL 4 and TEL 4a) is shown compared to the uptake of a cell using a control electrolyte composition (sample TEL 0).
[0101] Figure 2a A graph showing cathode discharge capacity (mAh / g) versus cycle number to illustrate the long term cycling performance at C / 5 of 10 mAh cells using the electrolyte compositions of the present invention (samples TEL 3, TEL 3a, TEL 4, and TEL 4a) compared to the cycling performance of cells using a control electrolyte composition (sample TEL 0).
[0102] Figure 2b A graph of cathode discharge capacity (mAh / g) versus cycle number for a 10 mAh full cell with a C / A mass balance of 1.4 is shown to provide a comparison of the performance of electrolyte compositions TEL 3b and TEL 4b with the performance of a cell using a control electrolyte composition (Sample TEL0).
[0103] Figure 3 A graph showing cathode discharge capacity (mAh / g) versus cycle number to illustrate the long term cycling performance of 5Ah cells using the electrolyte compositions of the present invention (Samples TEL 3a, TEL 4a) compared to the cycling performance of cells using a control electrolyte composition (Sample TEL 0).
[0104] Figure 4 A graph showing cathode discharge capacity (mAh / g) versus cycle number to illustrate the long term cycling performance of 10 mAh batteries using different electrolyte compositions (samples TEL 19, TEL 19a, TEL 19b, all not according to the present invention) compared to the cycling performance of batteries using a control electrolyte composition (sample TEL 0).
[0105] Figure 5a A graph showing cathode discharge capacity (mAh / g) versus cycle number to illustrate the long term cycling performance of 10 mAh batteries comprising different electrolyte compositions (sample TEL 19 not according to the invention and samples TEL 24, TEL 24a according to the invention) compared to the cycling performance of batteries using a control electrolyte composition (sample TEL 0).
[0106] Figure 5b A graph showing the cathode specific capacity (mAh / g) versus the number of cycles to illustrate the long-term cycling performance of 0.6Ah cells containing different electrolyte compositions (sample TEL19 not according to the invention, sample TEL 24 according to the invention) compared to the cycling performance of cells using a control electrolyte composition (sample TEL 0).
[0107] Figure 6 A graph showing cathode discharge capacity (mAh / g) versus cycle number to illustrate the cycling stability of cells containing different electrolyte compositions of the present invention (samples TEL 24, TEL24a) in the 3.75 to 2.5 V window compared to the cycling performance of cells using a control electrolyte composition (sample TEL 0).
[0108] Figure 7a A graph showing cathode discharge capacity (mAh / g) versus cycle number to illustrate the cycling performance of different electrolyte compositions (sample TEL 19 not according to the invention and samples TEL 24, TEL 24a, TEL 37, TEL 38a according to the invention) in the 4.2 to 1.0 V window compared to the cycling performance of cells using a control electrolyte composition (samples TEL 0, TEL 36, TEL 38).
[0109] Figure 7bA graph showing cathode discharge capacity (mAh / g) versus cycle number to illustrate the cycling performance of different electrolyte compositions (Sample TEL 39 not according to the invention and Sample 39a according to the invention) in the 3.75 to 2.5 V window compared to the cycling performance of a cell using a control electrolyte composition (Sample TEL 0).
[0110] Figure 8 A graph showing cathode discharge capacity (mAh / g) versus cycle number to illustrate the cycling performance of different electrolyte compositions (samples TEL 19, TEL 34 and TEL 35 not according to the invention and samples TEL 17, TEL 17b, TEL 24 and TEL 24a according to the invention) in the 4.2 to 1.0 V window compared to the cycling performance of a cell using a control electrolyte composition (sample TEL 0).
[0111] Fig. 9 The electrolyte absorption of ND525 separator (Asahi Kasei Corporation) for electrolyte compositions (samples TEL 2, TEL 2a not according to the invention and samples TEL 9 and TEL 10 according to the invention) is shown compared to the absorption of cells using control electrolyte compositions (samples TEL 0, TEL 1a).
[0112] Fig.10 A graph showing cathode discharge capacity (mAh / g) versus cycle number is shown to illustrate large scale pouch cell cycling performance of an electrolyte composition (Sample TEL 2 not according to the invention).
[0113] Fig.11 A graph showing cathode discharge capacity (mAh / g) versus cycle number to illustrate the 3E cycling performance of an electrolyte composition (Sample TEL 2 not according to the invention) in the 4.0 to 1.0 V window.
[0114] Fig.12 Display potential (V vs. Na / Na + ) versus active anode capacity (mAh / g) to illustrate the first cycle Coulombic efficiency performance of the electrolyte compositions (sample TEL 2 not according to the invention and sample TEL 23 according to the invention) in a 3E full cell and within the 4.2 to 1.0 V window as compared to the cycling performance of a cell using a control electrolyte composition (sample TEL 0).
[0115] Fig.13A graph showing cathode discharge capacity (mAh / g) versus cycle number to illustrate the cycling performance of 10 mAh 2E cells using different electrolyte compositions of the present invention (samples TEL 2 and TEL 14b not according to the present invention and samples TEL 14c, TEL 17 and TEL 23 according to the present invention) compared to the cycling performance of cells using a control electrolyte composition (sample TEL 0).
[0116] Fig.14a Graphs showing cathode discharge capacity (mAh / g) versus cycle number and % Coulombic efficiency versus cycle number to illustrate the cycling performance of a 10 mAh 3E full cell using the electrolyte composition of the present invention, sample TEL 24b, compared to the cycling performance of cells using control electrolyte compositions (samples TEL 0 and TEL 0c).
[0117] Fig.14b Graphs showing cathode discharge capacity (mAh / g) versus cycle number and % Coulombic efficiency versus cycle number are shown to illustrate and compare the cycling performance of 10 mAh 3E full cells using the electrolyte composition samples TEL 24, TEL 24b and TEL 24c of the present invention.
[0118] Fig.15 A graph showing cathode discharge capacity (mAh / g) versus cycle number is shown to illustrate the cycling performance of a 2E 10 mAh pouch cell using an electrolyte composition sample TEL 40 not according to the present invention.
[0119] Fig.16 A graph showing cathode discharge capacity (mAh / g) versus cycle number to illustrate the cycling performance of a 2E 10 MH pouch cell using an electrolyte composition, Sample TEL 41, not according to the invention, compared to the cycling performance of a cell using a control electrolyte composition (Sample TEL 0).
[0120] Fig.17 A graph showing cathode discharge capacity (mAh / g) versus cycle number to illustrate the cycling performance of 2E 10 mAh pouch cells using the electrolyte composition samples TEL 37a, TEL 43, and TEL 43c of the present invention compared to the cycling performance of cells using a control electrolyte composition (sample TEL 0).
[0121] Fig.18 A graph showing cathode discharge capacity (mAh / g) versus cycle number to illustrate the cycling performance of 2E 1Ah pouch cells using electrolyte compositions not according to the present invention, sample TEL 19, and samples TEL 24, TEL 37a, and TEL 43 according to the present invention, compared to the cycling performance of cells using a control electrolyte composition (sample TEL 0).
[0122] Fig.19 A graph showing cathode discharge capacity (mAh / g) versus cycle number is shown to illustrate the cycling performance of 2E 0.1 Ah pouch cells using the electrolyte composition samples TEL 58a and TEL 43e of the present invention.
[0123] Fig. 20 A graph showing cathode discharge capacity (mAh / g) versus cycle number to illustrate the cycling performance of 2E0.1 Ah pouch cells using electrolyte composition samples TEL 24b, TEL 58a, TEL 43e and TEL 42d according to the invention and sample TEL 43g not according to the invention.
[0124] Fig.21 Display current (mA / cm 2 )Relative voltage (V relative to Na / Na + ) to illustrate the cycling performance of 3E 10mAh pouch cells using samples TEL24 and TEL 37e of the electrolyte compositions of the present invention compared to the cycling performance of cells using control electrolyte compositions (samples TEL 0 and TEL 36).
[0125] Fig. 22 A graph showing cathode discharge capacity (mAh / g) versus cycle number to illustrate the cycling performance of 2E 0.1 Ah pouch cells using the electrolyte composition samples TEL 24b, TEL 61 and TEL 61b of the present invention.
[0126] Fig.23 A graph showing cathode discharge capacity (mAh / g) versus cycle number is shown to illustrate the cycling performance of a 2E 10 mAh pouch cell using an electrolyte composition, Sample TEL 44b, not according to the present invention, compared to the cycling performance of a cell using a control electrolyte composition (Sample TEL 0).
[0127] Details
[0128] The electrolyte compositions studied were prepared using the following general procedure: The appropriate amount of solvent for the desired solvent system was weighed out and added to a brown glass bottle in an argon-filled glove box. To thoroughly dry the formed solvent, Molecular sieves (Sigma-Aldrich) and the solvent mixture is dried for at least 24 hours. Afterwards, the solvent mixture is transferred to another brown glass bottle equipped with a magnetic stirrer while still in the glove box. Then the correct amount of one or more sodium-containing compounds are weighed out in an argon-filled glove box and slowly added to the solvent mixture under continuous stirring. Stir the electrolyte mixture until the salt is visually determined to be dissolved on the magnetic stirrer plate. The electrolyte mixture is then removed from the stirrer plate and stored and used in an argon-filled glove box.
[0129] The exact composition of each electrolyte composition investigated is detailed in Table 1 below:
[0130] Table 1
[0131]
[0132]
[0133]
[0134]
[0135] Abbreviations used:
[0136] EC = ethylene carbonate, DEC = diethyl carbonate, PC = propylene carbonate, TMP = trimethyl phosphate, PCS = 1,3-propylene glycol cyclic sulfate, P123 = Poloxamer (Pluronic) P123, F127 = Poloxamer (Pluronic) F127, TEP = triethyl phosphate, HFE = 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether, TMSB = tris(trimethylsilyl)borate, D2 = 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether, tetraglyme = tetraethylene glycol dimethyl ether.
[0137] Please note that in Table 1 above, the weight % of the various solvents and / or additives mentioned are relative to the total solvent weight (they do not account for the weight(s) of the sodium-containing salt(s)).
[0138] Battery Construction
[0139] General procedure for making hard carbon sodium-ion batteries
[0140] A sodium-ion pouch cell was constructed using active material electrodes, a separator, and an electrolyte; an aluminum sheet was connected to each electrode, and the cell was housed in a polymer-coated aluminum pouch.
[0141] The positive (cathode) electrode is prepared by solvent casting a slurry of active material, conductive carbon, binder and solvent. The conductive carbon used is C65 (Imerys). PVdF copolymer (e.g. W#7500 from Kureha Chemicals) is used as a binder, and NMP is used as a solvent. The slurry is then cast onto carbon-coated aluminum foil and dried at about 80°C. The electrode film contains the following components, expressed in weight percentage: 89% active material, 5% C65 carbon and 6% W#7500 binder.
[0142] The hard carbon negative (anode) electrode was prepared by solvent casting a slurry of hard carbon active material (Kuranode Type 1, provided by Kureha), conductive carbon, binder and solvent. The conductive carbon used was C65 (Imerys). PVdF copolymer (e.g. W#9300, Kureha Chemicals) was used as a binder, and NMP was used as a solvent. The slurry was then cast onto carbon-coated aluminum foil and dried at about 80°C. The electrode film contained the following components, expressed in weight percentage: 88% active material, 3% C65 carbon and 9% W#9300 binder.
[0143] Battery Test
[0144] The cells were tested using a constant current (galvanostatic) cycling technique as follows.
[0145] The battery was cycled at a given current density between preset voltage limits (at the top of the charge, a constant voltage step was applied). A commercial battery cycler from Maccor Inc. (Tulsa, OK, USA) was used. During charging, alkali ions are inserted into the anode material. During discharge, alkali ions are precipitated from the anode and reinserted into the cathode active material.
[0146] Experiment 1: Investigation of the effect of surfactants on the absorption of electrolyte compositions by separators and on the wettability of electrolyte compositions on hard carbon anode electrodes.
[0147] Two block copolymer nonionic surfactant materials, poloxamer (Pluronic) P123 and poloxamer (Pluronic) F127 were studied. Electrolyte compositions TEL 3, TEL 3a, TEL 3b, TEL 4, TEL 4a, TEL 4b, TEL 9, TEL 10 as shown in Table 1 above were prepared, and the absorption of each of these samples by a separator (Asahi ND525) and a hard carbon electrode (Type 1 hard carbon of Kuraray) was measured, and the results were compared with the absorption of a control electrolyte composition sample TEL 0 without a surfactant.
[0148] The electrolyte absorption value is calculated using the following:
[0149]
[0150] Where M0 is the weight of the bare separator (or hard carbon electrode), and M is the weight of the separator (or hard carbon electrode) after soaking it in electrolyte. For this purpose, all separators / electrodes were immersed in the electrolyte bath for 1 hour. The standard deviation was calculated from 3 different measurements:
[0151] like Figure 1a and 1b As shown in the results in , in the case of a surfactant-containing electrolyte, the electrolyte absorption on both the separator and the hard carbon (respectively) increases. Specifically, from Figure 1a and 1b It is evident from the Figures that the addition of 0.2 wt%, 1 wt% or 2 wt% of P123 or F127 surfactants to the TEL 0 electrolyte results in a 5-50% enhancement in electrolyte uptake on the separator and about 9% enhancement in electrolyte uptake on the hard carbon electrode.
[0152] These are statistically significant values and Example 2 below was used to test whether the improved absorption translates into better electrochemical performance.
[0153] Experiment 2: Cycling performance of a battery using an electrolyte composition containing a surfactant.
[0154] Using the general method described above, 10 mAh test cells were prepared using each of the sample electrolyte compositions TEL 3, TEL 3a, TEL 4, TEL 4a, and the control electrolyte composition TEL 0. The electrochemical performance of each test cell was then studied by cycling between 4.2 and 1.0 V. Figure 2a From the results shown in , it is clear that 1 wt % P123 or F127 provides longer cycle life than 0.2 wt % P123 or F127 and both weight percentages of surfactant outperform the performance of TEL 0. The best performance was observed for cells containing electrolyte composition TEL 3a (1 wt % P123) and this was slightly better than the performance of TEL 4a (1 wt % F127).
[0155] from Figure 2b It can be seen that further increasing the surfactant additive to 2 wt% significantly reduces the performance, and samples TEL 3b and TEL 4b result in similar performance degradation compared to the results for cells using the control electrolyte composition TEL 0.
[0156] Figure 3Long-term cycling data for large-scale 5Ah cells using TEL0, TEL3a or TEL4a electrolyte compositions are shown, and a trend toward enhanced cycle life when 1 wt% P123 or F127 surfactants are used, even in large-scale 5Ah cells. An enhanced cycle life of 51 cycles was also observed for cells using electrolyte composition TEL3a compared to similar cells using electrolyte composition TEL0.
[0157] Taking all factors into consideration, Figures 2 and Figure 3 The results shown in lead to the conclusion that 1 wt % P123 surfactant additive (TEL 3a) significantly improves the electrochemical performance.
[0158] Experiment 3: Study on the cycle performance of a battery using an electrolyte composition containing a sulfur-containing compound.
[0159] 1,3-Propanediol cyclic sulfate (PCS) was added to the control electrolyte composition TEL 0 to prepare electrolyte composition samples, namely: TEL 19 not according to the invention (1 wt % PCS), TEL 19a (2 wt % PCS) and TEL 19b (3 wt % PCS).
[0160] like Figure 4 As shown, all PCS-containing samples (TEL19, TEL19a and TEL19b) gave better cycling performance in terms of delivered capacity (capacity enhancement of approximately 10 mAh / g over that observed for cells using TEL0) and cycle life (cycle life enhancement of 40-120 cycles was obtained over that for cells using TEL0) compared to the performance of the control electrolyte composition sample TEL0.
[0161] It was also observed that the samples containing PCS gave a first cycle Coulombic efficiency that increased from 77% (for cells using TEL 0 electrolyte composition) to 80% (for cells using TEL 19, 19a, and 19b electrolyte compositions). This increase in performance can explain the higher capacity observed for PCS-based electrolytes, as less amount of Na from the cathode + is irreversibly consumed.
[0162] The best cycling performance was observed for the cell using the electrolyte composition containing 1 wt % PCS additive (sample TEL 19).
[0163] Experiment 4a: Study on the cycling performance of a 10 mAh battery using an electrolyte composition comprising a sulfur-containing compound (PCS) and a surfactant.
[0164] The long-term cycling performance of 10 mAh batteries containing an electrolyte composition of TEL 0 (control), or a composition of TEL 0 with 1% PCS (sample TEL 19), or a composition of TEL 0 and 1 wt % PCS + 1 wt % P123 (sample TEL 24), or a composition of TEL 0 and 0.5 wt % PCS + 0.5 wt % P123 (sample TEL 24a) was studied.
[0165] from Figure 5a It can be seen that the addition of the sulfur-containing compound PCS and the surfactant poloxamer P123 results in improved cycling performance compared to the cycling performance of the battery containing the control electrolyte composition TEL 0. It is particularly striking that the battery containing the TEL 24 electrolyte composition even outperforms the battery containing the TEL 19 electrolyte composition by 72 cycles. In addition, the battery containing the TEL 24 battery electrolyte composition results in a cycle life enhancement of 191 cycles (an enhancement of 72%) relative to the TEL 0 control battery. However, it can be seen that TEL 24 is the best performing sample, highlighting the benefit of increasing the surfactant weight percentage from 0.5 wt % (for TEL 24a) to 1 wt % (for TEL 24).
[0166] Experiment 4b: Study on the cycling performance of a 0.6 Ah battery using an electrolyte composition comprising a sulfur-containing compound (PCS) and a surfactant.
[0167] The long term cycling performance of larger scale 0.6 Ah cells containing electrolyte compositions of TEL 0 (control), or compositions of the invention: TEL 0 with 1% PCS (sample TEL 19), or TEL 0 and 1 wt % PCS + 1 wt % P123 (sample TEL 24) were further investigated.
[0168] like Figure 5b As shown in , the good performance of the TEL 24 shown in Experiment 5a above was also achieved with a larger 0.6Ah battery. Figure 5b The results presented in suggest that the cycle life of cells using 1 wt % PCS additive (TEL 19 or TEL 24) is likely to be longer than that of cells using TEL 0, based on the Figure 5b The capacity of the cell is shown as the position of the maximum value in the cycle number as a "hump". Specifically, it is noted that the position of the "hump" along the x-axis increases from the 77th cycle of TEL 0 to the 134th cycle of TEL 24 (an increase of 57 cycles). For the TEL 19 cell, the maximum value is reached after 140 cycles.
[0169] Figure 6Cycling stability within the 3.75-2.5V window is shown to simulate the voltage profile of starter-ignition-lighting (SLI) batteries used in current automobiles. In particular, for cells with a C / A mass balance of 2.27, electrolyte compositions TEL 24 and TEL 24a result in significantly higher capacities within the 3.75-2.5V window than similar control cells using electrolyte composition TEL 0 cycled under similar voltage conditions. Specifically, the control cell using electrolyte composition TEL 0 delivered a capacity of 50.4 mAh / g at cycle 60, while the cell using electrolyte composition TEL 24 delivered 53.1 mAh / g, and the cell using electrolyte composition TEL 24a delivered 54.3 mAh / g.
[0170] Advantageously, it was also found that the transport capacity could be further enhanced by increasing the C / A mass balance from 2.27 to 2.61 and 2.95.
[0171] Experiment 5a: Investigation of the effect of including propylene carbonate as the sole organic carbonate-based solvent in the electrolyte composition on the cycling performance of a 10 mAh cell.
[0172] The long-term cycling performance of batteries using an electrolyte composition comprising pure propylene carbonate (control sample TEL 36) or a mixture of propylene carbonate and 1 wt % PCS and 1 wt % P123 (sample TEL 37), or a control electrolyte composition (control sample TEL0) for 10 mAh between 4.2 and 1 V was studied.
[0173] like Figure 7a As shown in the results, the electrolyte composition control sample TEL 36 containing propylene carbonate as the only organic carbonate-based solvent (and no other second solvent component additives) provides poor cycle stability compared to the battery using the control electrolyte TEL 0. However, compared to similar batteries using the control electrolyte TEL 0, the electrolyte composition (sample TEL 37) containing propylene carbonate as the only organic carbonate-based solvent but also containing 1 wt% PCS and 1 wt% P123 additives provides a higher initial discharge capacity and better cycle stability in 60 cycles. This result shows that the pure PC-based electrolyte composition is particularly effective in hard carbon-based sodium-ion batteries when surfactants and sulfur-containing additives are also present.
[0174] Experiment 5b: Study on the effect of using an electrolyte composition without propylene carbonate on the cycle performance of a 10 mAh battery.
[0175] The long-term cycling performance of a 10 mAh battery between 4.2 and 1 V was studied, the battery using an electrolyte composition having a first solvent component, wherein the first solvent component comprises ethylene carbonate and diethyl carbonate (i.e., no propylene carbonate) (control sample TEL 38), or ethylene carbonate and diethyl carbonate (i.e., no propylene carbonate) with 1 wt % PCS and 1 wt % P123, (sample TEL 38a), or a control electrolyte composition (sample TEL 0).
[0176] like Figure 7a As shown, the cycling performance of the non-PC-based electrolyte composition (sample TEL 38a) containing 1 wt% PCS and 1 wt% poloxamer P123 provided significantly higher capacity (112.4 mAh / g) in the 5th cycle (after 4 formation cycles at C / 10) and significantly enhanced cycling stability, relative to a comparable battery using an electrolyte composition (sample TEL 38) having the same EC:DEC solvent but without the addition of PCS and surfactants, which showed very poor cycling stability and much lower 5th cycle capacity (97.5 mAh / g). This result shows that the electrochemical performance of the electrolyte composition containing organic carbonates can be significantly enhanced by including sulfur-containing compounds and surfactant additives.
[0177] The long-term cycling performance of two electrode (2E) 10 mAh cells between 3.75 and 2.5 V was also studied, the cells using an electrolyte composition having a first solvent component comprising ethylene carbonate and diethyl carbonate not according to the present invention (i.e., no propylene carbonate) and TMP (1:1 w / w) (sample TEL 39), or ethylene carbonate and diethyl carbonate (i.e., no propylene carbonate) and TMP (1:1 w / w) (sample TEL 39) with 1 wt% PCS and 1 wt% P123 (sample TEL 39a according to the present invention), or a control electrolyte composition (sample TEL 0
[0178] like Figure 7b As shown in the results, the non-PC-based TEL, TEL 39 and TEL 39a (using 50 wt% EC:DEC solvent and 50 wt% TMP) exhibited stable and significantly higher capacities in the initial cycle relative to the TEL 0 cell, indicating that the TMP-based electrolyte is highly compatible with the non-PC-based solvent. The results also confirmed that the inclusion of PCS and P123 additives resulted in similar stable cycling and higher capacities, and further demonstrated that such non-PC-based electrolyte compositions are likely to be useful for starter-ignition-lighting (SLI) batteries.
[0179] Experiment 6: Study on the effect of using different sulfur-containing compounds in their electrolyte compositions on the cycling performance of 10 mAh batteries.
[0180] The long-term cycling performance of a 10 mAh battery was studied between 4.2 and 1 V, using an electrolyte composition comprising an organic carbonate: sulfolane in a weight / weight ratio of 1:1 with 1 weight % of surfactant P123 (sample TEL 17), or a mixture of 5 weight % sulfolane and 1 weight % of surfactant P123 (sample TEL 17b), or 1 weight % 1,3-propanediol cyclic sulfate (sample TEL 19 not according to the present invention) or 1 weight % 1-propylene 1,3-sultone (sample 34), or 1 weight % 1,3-propane sultone (sample TEL 35 not according to the present invention), or a control electrolyte composition (control sample TEL 0).
[0181] like Figure 8 As shown in the results in , the electrolyte compositions containing sulfolane-based compounds (samples TEL17 and TEL17b) cycle well and are expected to be non-flammable through the presence of sulfolane. Although the cycling stability is reduced compared to the control electrolyte composition TEL0, this is expected to improve with the optimization of sulfolane-containing cells. In addition, as discussed later in Experiment 11, the cycle life of the cells using TEL17 in the 3.75-2.5V window can be as good as that seen with the control TEL0 cells (see Fig.13 ), therefore, the sulfolane-based electrolyte can still show excellent cycle stability. Compared with the cycle results of similar batteries using the control electrolyte composition TEL 0, electrolyte samples 34 and 35 both show enhanced initial discharge capacity and cycle stability (over 180 cycles).
[0182] Experiment 7: Study on the flammability of electrolyte compositions containing trimethyl phosphate.
[0183] Four different electrolyte compositions were prepared, one comprising a control electrolyte composition TEL 0, another comprising a control electrolyte composition TEL 0+, another comprising a 1:1 weight / weight mixture of (EC:DEC:PC=1:2:1 weight / weight):trimethyl phosphate (sample TEL 2), and a fourth comprising a 1:1 weight / weight mixture of (EC:DEC:PC=1:3:1 weight / weight):trimethyl phosphate (sample TEL 2a). The same amount of each electrolyte composition was then directly ignited with a lighter, and the time elapsed between the moment the electrolyte composition ignited and the moment it completely self-extinguished was recorded and used to calculate the "self-extinguishing time" (SET). Each of the four electrolyte compositions was tested three times, and the results were used to generate an average SET for each composition. A SET of <6s / g is associated with a non-flammable electrolyte composition. The SET of each electrolyte composition tested is detailed in Table 2 below:
[0184] Table 2
[0185]
[0186]
[0187] As can be readily seen from the results shown in Table 2, the electrolyte composition samples TEL 2 and TEL 2a containing trimethyl phosphate (TMP) are non-flammable and therefore are very advantageous over compositions without TMP.
[0188] Experiment 8: A study testing the effect of adding trimethyl phosphate to the electrolyte composition on the absorption of Ashai ND525 separator.
[0189] Electrolyte composition samples TEL 0, TEL 1a, TEL 2, TEL 2a, TEL 9 and TEL 10 (compositions as detailed in Table 1 above) were prepared and their absorption by Ashai ND525 separator was measured.
[0190] like Fig. 9 As shown, all TMP-containing electrolyte compositions exhibited higher membrane absorption than the control composition TEL0. The absorption results for TEL 2 and TEL 2a were about 20% higher than that for TEL 0, but even greater absorption was observed for the compositions containing trimethyl phosphate and a surfactant, with samples TEL 9 and TEL 10 improving by about 28% and more than 70%, respectively, relative to TEL 0. Based on these results, it is confidently expected that other TMP+surfactant-based electrolyte compositions, such as TEL14c and TEL 23, will also advantageously exhibit high absorption by the separator.
[0191] Experiment 9: Study on the electrochemical performance of a 0.5 Ah battery using an electrolyte composition containing trimethyl phosphate.
[0192] Long term cycling performance (between 4.2-1 V) of 0.5 Ah cells with C / A mass balances 1.52, 1.94 and 2.26 and electrolyte composition TEL 2 (a combination of electrolyte composition TEL 0 and trimethyl phosphate (TMP) in a solvent ratio of 1:1 w / w).
[0193] like Fig.10 As shown, the cycle life of the TMP-containing battery using the electrolyte composition TEL 2 increases from about 185 cycles to about 300 cycles when the mass balance of the battery increases from 1.52 to 2.26.
[0194] As from Fig.11As can be seen, the cycle life of the TMP-based TEL 2 can be further enhanced if cycled between 4V-1V. Under these derating conditions, the conventional GSM 1 type hard carbon anode (83GSM activity) and the low GSM 1 type hard carbon anode (52GSM activity) showed excellent cycle stability over 400 cycles with a capacity retention of 88%. Therefore, within the 4-1V window, TMP-based electrolytes can produce very stable cycles, with the additional benefit that these sodium-ion batteries will also be non-flammable.
[0195] Experiment 10: The electrochemical performance of an electrolyte composition containing 1,3-propylene glycol cyclic sulfate as a sulfur-containing compound and NaPF6 as a sodium-containing compound was studied.
[0196] The first cycle Coulombic efficiency of three-electrode (3E) full cells using electrolyte compositions TEL 2 and TEL 23 was studied between 4.2 and 1 V and the results were compared to those of similar cells using the control TEL 0 electrolyte composition.
[0197] like Fig.12 As shown, the PCS+P123+TMP based electrolyte composition (TEL 23, according to the invention) yields improved first cycle efficiency compared to TEL 2 (not according to the invention) and TEL 0 (control sample).
[0198] Experiment 11: The electrochemical performance of a 2E 10 mAh battery was studied to compare the effects of the electrolyte composition according to the present invention on the electrochemical performance.
[0199] 2E 10 mAh cells were prepared using electrolyte compositions TEL 2, TEL 14b, TEL 14c, TEL 17 and TEL 23 and results for long term cycling performance (between 3.75-2.5 V) were obtained and compared to cycling results for similar cells using control electrolyte composition TEL 0.
[0200] As mentioned above, the 3.75-2.5V window simulates the voltage curve of the starter-ignition-lighting (SLI) battery used in current automobiles, so Fig.13 The results shown in are very favorable, indicating that the electrolyte compositions comprising TMP and NaBF4 (samples TEL 14b, TEL 14c) and the composition comprising sulfolane and surfactant P123 (TEL 17) are very suitable for this end-use application. Under these voltage conditions, the electrolyte composition TEL 2 also shows excellent cycling stability at 300 cycles.
[0201] Thus, it was demonstrated that NaBF4 can be used instead of NaPF6 (sample TEL14b), and that NaBF4-based TMP electrolytes are also compatible with 1 wt% PCS and 1 wt% P123 additives (TEL14c). The electrolyte compositions of the present invention are expected to provide significant cost savings and greater flexibility in electrolyte salt selection.
[0202] Experiment 12: The charge acceptance of a sodium ion battery using the electrolyte composition according to the present invention was studied.
[0203] Charge acceptance is of significant commercial importance for any battery technology as it determines how quickly a battery can be safely charged. Fast charging increases the likelihood of alkali metal plating on the anode in alkali-ion batteries (especially if low voltage anodes are used), and this can lead to explosions - a fact well known to anyone skilled in the art. While it is generally known in the art of lithium-ion batteries that increasing electrolyte conductivity by increasing salt concentration can affect charge acceptance, no such demonstration has been shown before in the sodium-ion system. Fig.14a An example showing how the charge acceptance of a sodium ion battery can be enhanced by increasing the salt concentration. In this example, a 3E 10mAh battery is charged at various rates as shown, with the discharge cycle always at C / 5 (operating temperature of 30°C). Within the 4-1V window, it can be seen that TEL 0c can achieve fast charging at 2.5C or 3C, but TEL 0 causes rapid capacity decay over 2C due to sodium plating on the hard carbon anode (the low coulombic efficiency of TEL 0 at 2.5C and 3C shown in the figure on the right can be used as a representative of sodium plating). In addition, the electrolyte composition TEL24b according to the present invention achieves even better capacity retention than TEL 0c at fast 2.5C and 3C charging rates - if charged at 3C, the TEL 24b battery can provide 90.2mAh / g, instead of 87.5mAh / g for the TEL 0c battery under similar conditions.
[0204] Fig.14bThe above insights are extended to additional embodiments of the present invention to show 3E 10mAh full cell fast charge cycling data for sodium ion batteries cycled at 4.2-1V using three electrolytes: TEL 24 (0.5m NaPF6), TEL 24b (1m NaPF6), and TEL 24c (1.5m NaPF6). As previously mentioned, the three cells were charged at various rates as shown above, and the discharge cycle was always at C / 5 (operating temperature was 30°C). While the TEL 24 cell (A3PC377) exhibited a sharp drop in capacity after 1C, this did not occur with the TEL 24b cell (A3PC402) and the TEL 24c cell (A3PC398). In fact, it can be seen that TEL 24c exhibits the most excellent charge acceptance characteristics at different rates: the discharge capacity of A3PC398 at the 26th cycle at 3C rate is 112.3 mAh / g, while the corresponding value of A3PC377 is only 54.8 mAh / g, or only 49% of the value obtained for A3PC398.
[0205] These results demonstrate that embodiments of the present invention can lead to excellent charge acceptance of sodium ion batteries even at fast rates and under varying voltage windows. From these experiments, it is obvious to any person skilled in the art that even faster charge acceptance can be achieved using such an electrolyte by changing the C / A mass balance and voltage window of the battery. In addition, it is obvious to any person skilled in the art that alternative charging modes such as tapered charging (ultrafast charging rate such as 4C or 10C to a set % SOC such as 60 or 80% SOC, then reducing the charge rate to a lower value, such as 2C or C / 5 to 80, 90 or 100% SOC) will also be possible using the results disclosed herein.
[0206] Experiment 13: Investigation of the electrochemical properties of an alternative polyalkyl phosphate-containing electrolyte sample TEL 40 (not according to the invention).
[0207] Fig.15 Long term cycling of a 2E10 mAh cell using TEL 40 electrolyte (not according to the invention) containing TEP is presented. It will be appreciated that TEP belongs to the same family of polyalkyl phosphates as the embodiments of the invention comprising TMP discussed in Experiments 7-9. Fig.15 If TEL 40 is used as the electrolyte, the APFC221 battery can achieve a cycle life of 196 cycles at a C / A mass balance of about 1.4, reaching a capacity decay of 20%. Fig.10, it can be seen that a cell FPC1 80622 using TEL 2 having a similar C / A mass balance (1.52 vs. 1.4) as that used for APFC221 can produce a cycle life of about 175 cycles (TEL 2 is a TMP-based electrolyte). As has been demonstrated in Experiment 9, increasing the C / A mass balance of the TMP-based electrolyte significantly improves the cycle life of otherwise similar cells. Since TEP belongs to the same solvent family as TMP, it will be apparent to anyone skilled in the art that a TEP-based electrolyte can also produce a longer cycle life if the C / A mass balance is appropriately adjusted (increased, for this particular cathode / anode combination).
[0208] Experiment 14: Study using diluted solvent HFE sample TEL 41 (not according to the invention).
[0209] In order to enhance electrolyte performance by reducing the overall electrolyte viscosity, Fig.16 Long term cycling of a 2E10 mAh cell using TEL 0 (APFC76) was compared to APFC222 using TEL 0 with 50 wt% hydrofluoroether HFE (TEL 41). From the prior art of highly concentrated lithium ion electrolytes, where the salt concentration is typically >4 M, it has recently been determined that HFE is a good diluting solvent that does not change the nature of the salt interaction with the base solvent(s), while also being low cost and having good electrochemical and thermal stability. Therefore, as any technician in the field will recognize, reducing the overall viscosity of the electrolyte can enhance the performance of alkaline ion batteries. Regarding the concept of dilution, there is no prior art for diluting sodium ion electrolytes using non-metallic (sodium) based anodes. Therefore, it would not be obvious to anyone skilled in the art that adding some amount of such dilute solvents to an established dilute electrolyte such as those discussed previously in this patent disclosure would enhance the performance of the resulting sodium ion battery or degrade its performance (it is not easy to predict how its hydrofluoroethers would interact with the many known sodium ion non-sodium metal anodes, such as carbon-based anodes or alloy-based anodes, to name just a few). To clarify this issue, reference is made to Fig.16 It is clear that APFC222 containing the diluent-based TEL 41 is superior to APFC76 containing the control TEL 0 electrolyte because it has a higher initial discharge capacity (107.5 mAh / g vs. 105 mAh / g) and a longer cycle life to 20% capacity fade (cycle 288 vs. cycle 265). Therefore, this experiment has determined that the addition of a dilute hydrofluoroether solvent to a commercial sodium-ion electrolyte even further enhances the performance of the resulting sodium-ion electrolyte.
[0210] Experiment 15a: Study on the use of dilute solvent HFE in PC-based electrolyte according to the present invention: small 10 mAh pouch cell.
[0211] According to an embodiment of the present invention, Experiment 15a extends Experiment 14 to the field of sodium ion electrolyte containing a large amount of PC as a solvent. Fig.17 Long term cycling of 2E 10 mAh all-Na-ion cells using TEL 0 (control), TEL 37a (PC-based electrolyte with 2 wt% PCS and 1 wt% P123 surfactant additives), TEL 43 (TEL 37a with 20 wt% HFE diluent), and TEL 43c (TEL37a with 40 wt% HFE diluent and 1 m NaPF6) are presented. It was previously determined in Experiment 5a that Na-ion electrolytes based solely on PC solvent with PCS and P123 additives outperformed the control TEL 0 and TEL 36 (PC electrolyte only, no additives) electrolytes (see Figure 7a ).about Fig.17 A relevant point to note is that these 10 mAh full cells were produced according to the following patent disclosure ('LIGHT GSM ANODE', PCT application number PCT / GB2019 / 053519) using a 52 GSM (5.2 mg / cm 2 ) of the hard carbon active material weight. In addition, as shown in the figure, all cells used Asahi ND525 separator, which is a standard polyolefin type separator for commercial lithium / sodium ion batteries. Fig.17 , it can be seen that of the 4 electrolytes shown, TEL0 has the lowest cycle life to 20% capacity fade (271 cycles), while TEL37a actually has the longest cycle life (389 cycles). Crucially, the two diluent-based electrolytes have longer cycle lives than the TEL0 electrolyte (304 cycles for TEL43 and 320 cycles for TEL43c), indicating that such PC+HFE-based electrolytes can outperform the control TEL0 electrolyte.
[0212] Experiment 15b: Study on the use of dilute solvent HFE in PC-based electrolyte according to the present invention: large-scale 1 Ah pouch cells.
[0213] Experiment 15b extends Experiment 15a to the field of large-scale sodium-ion pouch cells that will actually be used in commercial applications, such as 1 Ah pouch cells. Fig.18Long term cycling of such 1Ah cells at ±C / 3 rates at 30°C rates is shown using commercial Celgard 2500 separators (these are also commercially used polyolefin separators similar to Asahi ND525 separators, and it should be understood that the results obtained from such separators can be extended to all such commercially used polyolefin separators). Results for 5 different electrolytes have been shown. The control cell (FPC190601) using TEL 0 electrolyte exhibited a cycle life of 308 cycles to 20% capacity fade (in the legend, the cycle life to 20% capacity fade has been mentioned in brackets). The other four electrolytes are according to different embodiments of the present invention. Specifically, electrolytes based on a mixed carbonate co-solvent of EC:DEC:PC = 1:2:1 weight / weight with either PCS additive only (TEL 19 (not according to the invention); FPC190605), or with PCS and P123 additives (TEL 24; FPC190607 (according to the invention)) outperformed the control cells in 27-119 cycles, consistent with other disclosures previously mentioned in this patent. With respect to PC-based electrolytes, it should first be noted that the cell FPC190609 (PC-based, no dilution co-solvent) using TEL 37a did not cycle at all even during the C / 10 rate formation cycles (even though 0 mAh was obtained at C / 10). This result should be compared with the performance of the 10 mAh scale TEL37a in Experiment 5a (cell APFC243), where despite the use of a similar GSM hard carbon anode and a similar C / A mass balance, TEL37a produced a cycle life of 389 cycles at a faster cycling rate of ±C / 2. This result is unique for PC electrolyte only because compared Fig.17 The cycle life seen at the 10 mAh scale is shown (271 cycles), with the control TEL 0 electrolyte having a slightly longer cycle life at the 1 Ah scale (308 cycles).
[0214] The reason that the PC-based TEL 37a electrolyte does not cycle at all at the 1Ah scale is the well-known relatively high viscosity of the PC solvent - as demonstrated herein, this higher viscosity still enables small-scale batteries (such as the 10mAh pouch cells or Swagelok or coin cells that are predominantly used in the prior art) to function effectively, but when used in actual commercial-scale batteries, the high viscosity of the PC electrolyte alone imposes an insurmountable obstacle. In particular, the high viscosity of the PC electrolyte alone results in very poor electrolyte wettability on the polyolefin separators used in commercial cells. The only other way to make such a PC-only electrolyte work in large-scale batteries would be to use a glass fiber separator, which typically holds a large amount of electrolyte per unit weight - this may overcome the wettability problem, but will impose a serious weight (and cost) burden on the resulting battery, because a much larger amount of electrolyte is used in a battery of similar rated rate than is the case with a battery using a polyolefin separator. As a result, the resulting battery energy density will be significantly lower - which is clearly not commercially attractive. Therefore, anyone skilled in the art should understand that the prior art showing good performance of PC-only electrolyte (with / without small amounts of additives) in small-scale cells is not commercially relevant at all, and the burden of proving the commercial viability of such PC-only electrolyte should be on the specific prior art demonstrating the use of commercially relevant materials and methods at a commercial scale (large-scale cells). Keeping this in mind, Fig.18 Long term cycling of TEL 43 (according to the present invention), a PC-based electrolyte with 20 wt% HFE diluent and 1 wt% surfactant P123, is presented. As shown, the PC-based electrolyte can function very effectively with only 20 wt% HFE diluent and 1 wt% P123 - in fact, this cell FPC190610 provides the longest cycle life to 20% capacity fade to date (610 cycles), nearly doubling the cycle life of the control TEL 0 sample under similar conditions.
[0215] Experiment 16: Study on the use of alternative dilution solvents in the PC-based electrolyte according to the present invention.
[0216] Experiment 16 provides another example of a diluent that can be used to make PC-dominated electrolytes work in large-scale commercial sodium-ion batteries. Fig.19As shown in (in the legend, the cycle life at 20% capacity fade has been indicated), the cycle life at fast ±1C in the 4.2-1V window at 30°C was studied using either HFE-based TEL 43e (FPC200116) or D2-based TEL 58a (FPC191023) electrolytes. It can be seen that the cycle life at this fast 1C rate for both electrolytes is even higher than that seen for small-scale cells using the control TEL0 electrolyte at 4.2-1V: with these diluent-based PC-based electrolytes, even though the latter conditions are favorable (small-scale 10mAh cells and at slower ±C / 2 cycle rates, where the possibility of sodium plating is even smaller), if the control TEL 0 electrolyte (ref. Fig.17 and battery APFC89), a cycle life of about 467-562 cycles can be achieved, which is almost twice the cycle life of 271 cycles relative to the previous work.
[0217] Based on these results, it should be understood that other types of diluent solvents can also achieve such high performance from PC-dominated sodium ion electrolytes. Some examples include, but are not limited to, the following: other hydrofluoroethers, low viscosity ethers or carbonates or polyalkyl solvents with appropriate dielectric constants, inertness / stability, and coordination properties so that they do not significantly affect the solvation of the salt with the PC solvent while still affecting the physical properties of the resulting electrolyte.
[0218] Experiment 17: Study on the use of alternative additives in the PC+diluent based electrolyte according to the present invention.
[0219] Experiment 17 provides an example on the use of other types of electrolyte additives in a PC+diluent based electrolyte in an actual large scale 0.1 Ah pouch cell. Fig. 20Long term cycling of 0.1Ah cells at ±C / 2 within a 4.2-1V window at 30°C is presented, the cells using TEL24b, TEL 58a, TEL 43e and two new types of PC+HFE based electrolytes: TEL 42d (using 1 wt% PCS, 1 wt% P123 and 1 wt% TMSB additives), all according to the present invention, and TEL 43g (using only 2.5 wt% EC additives), not according to the present invention. It can be seen that the cycling characteristics of all cells in 150-180 cycles are very similar: all PC+HFE based electrolytes provide slightly better performance than TEL 24b, with TEL42d appearing to be the highest performing electrolyte by far, indicating the beneficial effect of replacing half of the PCS additive of TEL 43e with TMSB additive (to form TEL 42d). EC as an additive would be most advantageous in terms of cost, since EC is an expensive solvent that is typically used in large quantities in commercial lithium-ion and sodium-ion electrolytes. Obviously, in conventional electrolytes, EC itself is present as a co-solvent in a volume or weight percentage such as 20% or 50%. In the PC+diluent-based electrolyte disclosed herein, the choice of using EC as an inexpensive electrolyte additive with good electrochemical performance opens up the possibility of reducing the cost of the resulting battery, which will ultimately affect the cost / kWh of such a battery system. This makes commercial sense.
[0220] Experiment 18: Study on the oxidation stability of the PC-based electrolyte according to the present invention.
[0221] In addition to enhanced cycling stability, the move to PC-dominant electrolytes can have another positive effect - namely the effect that the oxidation stability of the electrolyte is generally higher, which will prevent the generation of smaller amounts of gas in such cells. It is well known in the prior art that EC has excellent reduction stability (at low voltages) but poor oxidation stability (at high voltages), especially for lithium-ion batteries: it is well known that EC decomposes on the surface of the graphite anode used in lithium-ion batteries to form a stable SEI. Although PC is known to have better oxidation stability in lithium-ion systems, PC-only or PC-dominant electrolytes cannot be used in lithium-ion batteries because PC causes the graphite anode to peel off, resulting in significantly poor cycling performance of such batteries. On the other hand, as mentioned earlier and demonstrated here in many examples, PC-only or PC-dominant electrolytes can actually achieve superior sodium-ion battery cycling compared to prior art EC-based sodium-ion electrolytes.
[0222] One of the reasons why this happens will be explained in Experiment 17 here, which quantitatively studies the oxidative stability of four sodium ion electrolytes by linear sweep voltammetry (LSV) loops. In these LSV experiments, 3E pouch cells were made with the same cathode and anode footprints as used in the 10 mAh pouch cells shown in several places in this disclosure, but with one major difference: both the cathode and anode were just pure Al current collector foils. In the LSV experiments, these cells were filled with the electrolyte of interest and subjected to a slow 2 mV / s scan rate to different upper cutoff potentials, then cycled down to 2.5 V, and then the process started again. Therefore, such experiments are a cross between cyclic voltammetry and LSV experiments. The advantage of such a modified LSV experiment is that one can accurately calculate the charge transferred due to electrolyte oxidation on the Al current collector at different V windows, such as 3.8-4.2 V, 4.2-4.4 V, 4.4-5 V, and 5-8 V. Since the electrodes are just pure Al current collector foils without active materials, in theory all the charge passed should be associated with electrolyte oxidation. In such an experiment, the lower the charge consumed, the less susceptible the electrolyte will be to oxidation, and therefore, the better the performance of the electrolyte should be when used in actual sodium-ion batteries charged to near these voltages. Although most of the batteries discussed in this document are cycled to 4V or 4.2V, it should be understood by any technician in the field that electrolyte oxidation is catalyzed by the presence of cathode active materials and conductive carbon present in the cathode, and the modified LSV experiment represents an ideal situation scenario that cannot be achieved in real-world scenarios. Therefore, it can be understood by any technician in the field that due to the catalytic effects of various components, in this modified LSV experiment (such as 4.4-5V and 5-8V), the charge consumed due to electrolyte oxidation at higher potential bands may be more representative of what the electrolyte actually experiences in terms of oxidation in actual sodium-ion batteries discussed in the present disclosure (which are typically charged to 4V or 4.2V).
[0223] As stated, Fig.21 and Table 3 present the results of modified LSV experiments on four electrolytes: TEL 0 and TEL 36 (control samples) and TEL 24 and TEL 37e as embodiments of the present invention.
[0224] Table 3
[0225]
[0226]
[0227] exist Fig.21In the figure, as indicated by the arrow, the lower the current at a specific voltage value, the higher the voltage value before the electrolyte completely breaks down (indicated by the exponential increase in current above 7V), and the less susceptible the electrolyte is to oxidation. Such kind of experiments are severely affected by the experimental scan rate - faster scan rates, such as 10mV / s (very frequently used in the literature), tend to underestimate the extent of electrolyte oxidation due to kinetic (polarization) effects. This is why a slow value of 2mV / s was chosen in this experiment to avoid such complications. According to Fig.21 It is qualitatively evident that both electrolytes formulated according to embodiments of the present invention along with the PC-based TEL 36 are superior relative to the control TEL 0 sample.
[0228] Table 3 provides quantitative values for the amount of charge Q (in mC) passed during oxidation of different electrolytes in the various voltage ranges shown. It is apparent from Table 3 that TEL 24, TEL 37e, and TEL 36 result in significantly less charge consumed due to electrolyte oxidation than that seen with the control TEL 0 electrolyte. For example, in the 4.4-5V range, TEL 24 consumes 30.4% less charge than TEL 0, indicating the positive role of PCS and P123 additives in protecting the base TEL 0 electrolyte from electrolyte oxidation (TEL 24 is only TEL 0 with PCS and P123 additives). Turning to PC-dominated electrolytes, TEL 36, which is purely PC-based and contains no additives, results in the lowest amount of charge passed in this voltage range (61.4% lower than the TEL 0 sample), while TEL 37e, which is based on PCS, P123, and EC additives, consumes 28.6% less charge than TEL 0. However, PC-only or PC-dominated electrolytes also benefit from the additives disclosed in this invention, and this can be understood by considering the total amount of charge passed across the 3.8-8V range: in this full voltage range, the TEL 37e actually shows the lowest electrolyte oxidation, and therefore, it is clear that additives such as PCS, P123 and EC help make PC-based electrolytes more resistant to oxidation. Fig.21 As can be seen from the figure, for both electrolytes according to the invention, the onset of complete electrolyte breakdown occurs at the highest potential: for the EC:DEC:PC=1:2:1 w / w solvent system, comparing TEL 24 with TEL 0 (for TEL 24, breakdown occurs at about 7.3 V vs. Na / Na + , but for TEL 0, breakdown occurs only at about 6.8 V vs. Na / Na + ), while for the PC-dominated electrolyte system, the breakdown of TEL37e and TEL 36 (for TEL 37e, the breakdown occurs at about 7.6 V vs. Na / Na +However, for TEL 36, breakdown only occurs at about 6.8 V relative to Na / Na + ). Therefore, any person skilled in the art will appreciate that the use of PC as a solvent alone is not sufficient to result in enhanced oxidative stability of the resulting electrolyte (and the cycling performance of the resulting sodium-ion battery); rather, it is the combination of PC with additives and diluents as detailed in the present disclosure that results in excellent oxidative stability and electrochemical cycling performance.
[0229] Such an oxidatively stable electrolyte will also ensure that the resulting sodium-ion battery does not exhibit significant gassing - as is well known to those skilled in the art of high voltage battery systems, the high voltages used in such batteries may result in significant gas generation due to electrolyte oxidation, and this gassing may then have serious adverse knock-on effects such as capacity degradation, metal plating due to uneven pressure distribution in a sealed cell, or in the worst case, severe explosion. Thus, such LSV experiments conclusively demonstrate that the additives mentioned in the present disclosure can significantly enhance the oxidative stability of sodium-ion electrolytes, regardless of the solvent system used.
[0230] The results contained in Experiments 15-18 also demonstrate for the first time that PC-dominant electrolytes together with suitable additives and diluent co-solvents disclosed herein can function effectively in large-scale commercial Na-ion batteries at low temperatures, with cycle lives much higher than current state-of-the-art electrolytes, results that were previously thought to be unattainable.
[0231] Experiment 19: Study on the use of alternative salts in the sodium ion electrolyte according to the present invention.
[0232] Fig. 22 Cycling results of large-scale 0.1Ah pouch cells cycled between 4-1V at 30°C at ±1C using a sodium ion electrolyte based on NaTFSI salt are presented. It can be seen that after 240 cycles, both TEL 61 (same as TEL 24b, but using NaTFSI salt instead of NaPF6 salt) and PC+HFE-based TEL 61b provide higher capacity than TEL 24b, indicating that NaTFSI can be an attractive salt that leads to even superior performance when combined with suitable solvents and additives as disclosed herein.
[0233] Experiment 20: Investigation using double salts in the sodium ion electrolyte TEL44b (not according to the invention).
[0234] Fig.23Cycling results of small-scale 10 mAh pouch cells cycled between 4.2-1 V at 30°C at ±C / 2 using TEL 0 (control sample) or dual salt TEL 44b (0.5 m NaPF6 in a mixture of carbonate, HFE diluent, and a tetraglyme-based pentasolvent system + 0.045 m NaBF4 in a mixture of carbonate, HFE diluent, and a tetraglyme-based pentasolvent system) are presented. The use of dual salts with three different types of solvent systems resulted in slightly higher sodium-ion cell capacities (about 116 mAh / g for APFC246) compared to TEL 0 cells (about 113 mAh for APFC 89), with similar cycling stability through 90 cycles.
[0235] Experiment 21: Study on the thermal stability (flash point test) of the sodium ion electrolyte according to the present invention.
[0236] In recent years, the flammability of commercial lithium-ion batteries has been well documented - there have been various reports of lithium-ion batteries catching fire and exploding in various applications such as different types of consumer electronics or electric vehicles. As is well known to those skilled in the art, one of the main causes of these fires / explosions in lithium-ion batteries is the high flammability of the liquid electrolytes used in them. In short, such commercial lithium-ion batteries use electrolytes with low flash points. The flash point is not an intrinsic physicochemical property of the liquid, but varies with the type of measurement technique and instrumentation used. As is well known in the art and described in various prior art, such as Hess et al. (Journal of The Electrochemical Society, 162 (2) A3084-A3097 (2015)), standardized closed cup flash point test methods, such as the Abel method (for liquids exhibiting a flash point between -30 and 70°C) and the Pensky-Martens method (for liquids exhibiting a flash point > 40°C) generally provide the most accurate results in terms of flash point testing. Therefore, these methods are also used herein, and the flash point measurement results are shown in Table 4 below.
[0237] Referring to Table 4, the first entry is that of a typical commercial lithium-ion electrolyte LP 30 (control sample). It can be seen that LP 30 obtained a flash point of 32°C, indicating that it is a flammable liquid and is consistent with previous reports such as Hess et al. In addition, two other control sodium-ion control electrolytes (TEL 0+ and 151) were also found to be flammable. The control TEL 0 electrolyte exhibited a higher flash point of 38.5°C, indicating lower flammability than the other control samples. Since TEL 24b is based on the same solvent system as the control TEL 0 and contains only PCS and P123 additives, it also provides the same flash point value of 38.5°C, indicating that these PCS and P123 additives do not affect the flash point. TEL 14d, based on the non-flammable TMP solvent, exhibits a higher flash point of 44°C, indicating its excellent thermal stability. Furthermore, as has been demonstrated in Experiment 7, the TMP-based electrolyte will self-extinguish very quickly even if it catches fire, indicating that such a TMP-based electrolyte is essentially non-flammable regardless of the flash point.
[0238] As expected, PC-dominated (TEL 43c, TEL 43e and TEL 58a) or PC+TMP-based (TEL 49d) electrolytes were found to be extremely thermally stable: in fact, no flash point was measured until 120°C, after which the test was stopped due to significant black smoke emissions. The results indicate that these PC-dominated electrolytes will decompose rather than ignite. From a battery safety perspective, this is very attractive in the presence of any catastrophic event that triggers thermal dissipation - the electrolyte simply decomposes rather than ignites, preventing an explosion. As another attractive point, increasing the diluent weight % from 20 wt % (for TEL 43e) to 40 wt % (for TEL 43c) does not affect the thermal behavior of the electrolyte. A higher proportion of diluent in the electrolyte blend will further reduce its viscosity and enhance the electrochemical performance without (as shown by the flash point results) affecting thermal stability. From a commercial perspective, this is obviously a huge benefit.
[0239] In summary, it has been demonstrated that, in addition to enhanced electrochemical performance, various embodiments of the present invention also result in significantly more thermally stable electrolytes.
[0240] Table 4
[0241]
Claims
1. A non-aqueous electrolyte composition comprising: a) one or more sodium-containing salts selected from sodium tetrafluoroborate (NaBF4), sodium hexafluorophosphate (NaPF6), sodium bis(fluorosulfonyl)imide (Na(SO2F)2N), sodium bis(trifluoromethanesulfonyl)imide (C2F6NNaO4S2); and b) a solvent system comprising: i) a first solvent component comprising one or more organic carbonate-based solvents; and ii) a second solvent component comprising one or more compounds selected from one or more hydrofluoroether compounds, one or more nitrile-containing compounds, one or more sulfur-containing compounds and one or more flame retardants, and wherein the one or more sulfur-containing compounds are selected from cyclic sulfones, non-cyclic sulfones and organic sulfates. 2 . The nonaqueous electrolyte composition according to claim 1 , wherein the one or more hydrofluoroether compounds comprise one or more hydrofluoroalkyl ether compounds.
3. The non-aqueous electrolyte composition according to claim 2, wherein the one or more hydrofluoroalkyl ether compounds comprise 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (HFE).
4. The non-aqueous electrolyte composition according to claim 1, wherein the cyclic sulfone and the non-cyclic compound are one or more selected from sulfolane, 3-methylsulfolane, trimethyl sulfone and methyl phenyl sulfone.
5. The non-aqueous electrolyte composition according to claim 1, wherein the organic sulfate is 1,3-propylene glycol cyclic sulfate (PCS).
6. The nonaqueous electrolyte composition of claim 1, wherein the one or more sulfur-containing compounds are present in an amount not greater than 60% by weight of the solvent system.
7. The non-aqueous electrolyte composition according to claim 1, wherein the one or more nitrile-containing compounds are selected from the group consisting of adiponitrile and glutaronitrile.
8. The non-aqueous electrolyte composition according to claim 1, wherein the second solvent component further comprises one or more compounds selected from one or more glyme and one or more glycol ether acetates.
9. The non-aqueous electrolyte composition according to claim 1, wherein the one or more flame retardants comprise one or more flame retardant materials, and the one or more flame retardant materials are one or more polyalkyl phosphate-containing compounds.
10. The non-aqueous electrolyte composition according to claim 9, wherein the one or more polyalkyl phosphate-containing compounds are one or more trialkyl phosphates, preferably trimethyl phosphate and / or triethyl phosphate.
11. The non-aqueous electrolyte composition of claim 9, wherein the one or more polyalkyl phosphate-containing compounds are present in an amount of at least 1 wt% to 90 wt% based on the total weight of the solvent system.
12. The non-aqueous electrolyte composition according to claim 1, wherein the one or more flame retardants comprise one or more flame retardant additives selected from dimethyl methylphosphonate (DMMP), ethoxy-pentafluoro-cyclotriphosphazene (N3P3F5OCH2CH3, EFPN), tris(2,2,2-trifluoroethyl)phosphite, tris(2,2,2-trifluoroethyl)phosphate (TFEP), methyl nonafluorobutyl ether (MFE) and silane-Al2O3 nanoparticles.
13. The non-aqueous electrolyte composition of claim 12, wherein the one or more flame retardant additives are present in an amount of <15 wt% based on the total weight of the solvent system.
14. The non-aqueous electrolyte composition according to claim 1, further comprising one or more surfactants.
15. The non-aqueous electrolyte composition of claim 14, wherein the one or more surfactants are present in an amount of >0.5 wt% to ≤10 wt% of the solvent system.
16. The non-aqueous electrolyte composition of claim 14, wherein the one or more surfactants are present in an amount of ≥ 0.6 to ≤ 6 wt% of the solvent system.
17. The non-aqueous electrolyte composition according to claim 14, wherein the one or more surfactants are selected from: Anionic surfactants selected from carboxylates, sulfates and sulfonates, wherein: The sulfonate is selected from docusate and alkylbenzene sulfonate; Selected from RN + H3Cl - , RN + (CH3)3Cl - , dioctadecyldimethylammonium chloride, cetylpyridinium chloride, benzalkonium chloride, cetyltrimethylammonium chloride (CTAC) and cetyltrimethylammonium bromide (CTAB); and A nonionic surfactant selected from the group consisting of polyol esters, polyoxyethylene esters, poloxamers and phosphate esters.
18. The nonaqueous electrolyte composition according to claim 1, wherein the organic carbonate-based solvent is one or more selected from propylene carbonate, diethyl carbonate, dimethyl carbonate, ethylene carbonate, ethyl methyl carbonate, fluoroethylene carbonate, and vinylene carbonate.
19. The non-aqueous electrolyte composition of claim 1, wherein the one or more sodium-containing salts are selected from sodium tetrafluoroborate (NaBF4) and sodium hexafluorophosphate (NaPF6).
20. A sodium ion battery comprising a negative electrode, a positive electrode and the nonaqueous electrolyte composition according to any one of claims 1 to 19.
21. A non-aqueous electrolyte composition comprising: a) one or more sodium-containing salts; and b) a solvent system comprising: i) a first solvent component comprising one or more organic carbonate-based solvents; and ii) a second solvent component comprising one or more surfactants.
22. The non-aqueous electrolyte composition of claim 21, wherein the one or more surfactants are present in an amount of >0.5 wt% to ≤10 wt% of the solvent system, preferably ≥0.6 wt% to ≤6 wt% of the solvent system.
23. The non-aqueous electrolyte composition according to claim 21 or 22, wherein the one or more surfactants are selected from: Anionic surfactants selected from carboxylates, sulfates and sulfonates, wherein: The sulfonate is selected from docusate and alkylbenzene sulfonate; Selected from RN + H3Cl-、RN + Cationic surfactants of (CH3)3Cl-, dioctadecyldimethylammonium chloride, cetylpyridinium chloride, benzalkonium chloride, cetyltrimethylammonium chloride (CTAC) and cetyltrimethylammonium bromide (CTAB); and A nonionic surfactant selected from the group consisting of polyol esters, polyoxyethylene esters, poloxamers and phosphate esters.
Citation Information
Cited By
Composite fiber diaphragm, preparation method and application thereof, and lithium ion battery
CN121035525A